2008
DOI: 10.1002/pds.1455
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of self‐medicated drug use among the Spanish adult population

Abstract: In Spain, the prevalence of self-medicated drug use is higher in women than men. In our population, the influence of unhealthy lifestyles, such as alcohol and tobacco consumption, is related to a higher likelihood of self-medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
79
6
17

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 21 publications
17
79
6
17
Order By: Relevance
“…In fact, individuals with a lower educational level and occupational status tended to misuse antibiotics while those with a higher level tended to abuse drugs. Other studies revealed similar (16) or lower rates (17), but equal predictive factors of self-medicated drug use. One could speculate that the attitude of the patient may reflect the level of knowledge concerning antibiotics.…”
Section: Self-prescription Non-adherence To Prescription ------------mentioning
confidence: 81%
“…In fact, individuals with a lower educational level and occupational status tended to misuse antibiotics while those with a higher level tended to abuse drugs. Other studies revealed similar (16) or lower rates (17), but equal predictive factors of self-medicated drug use. One could speculate that the attitude of the patient may reflect the level of knowledge concerning antibiotics.…”
Section: Self-prescription Non-adherence To Prescription ------------mentioning
confidence: 81%
“…Poor regulation of antimicrobials results from absent policies or, more commonly, from absent enforcement of policies, as happens in southern European countries. [51][52][53][54][55] Community antimicrobial resistance was common in several studies that examined communities with frequent use of nonprescription antimicrobials. [6][7][8][9][10][11] Antimicrobial use, whether it is prescription or non-prescription, exerts antimicrobial selection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Of seven European studies, [51][52][53][54][55][56][57] one surveyed 19 countries with at least 200 respondents per country. 52 Sufficient survey data were available to describe individual regions.…”
Section: Frequency Of Non-prescription Usementioning
confidence: 99%
See 1 more Smart Citation
“…Nonvignon et al [5] show that factors that could encourage self-medication include longer travel and waiting times at public health facilities. Non-prescription medicines also influence health status as perceived by an individual [6,7]. It is worth noting that perceived or self-assessed health has been shown to relate positively with health status and mortality [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%